2016
DOI: 10.1016/j.jpain.2016.01.060
|View full text |Cite
|
Sign up to set email alerts
|

(157) The association of sickle cell-related stigma with physical and emotional symptoms in patients with sickle cell pain

Abstract: interplay between these factors remains unclear. This study examined the role of catastrophizing in moderating the relationship between sleep (insomnia symptoms & objective measures of sleep continuity) and clinical and laboratory pain. 127 women with TMD were recruited as part of a larger study evaluating interventions for sleep and catastrophizing on pain. Participants underwent baseline testing, including self-report measures (clinical pain, depression, anxiety, catastrophizing, insomnia-severity), laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Patients with self-perceived higher levels of stigma noted increased levels of fatigue, anger, anxiety, and depression. 12 The findings of this study were confirmed with our survey, which showed that some of the barriers to patient care were that patients were in pain, tired, fearful, and angry or frustrated. This is further exacerbated by the well-documented racial and ethnic bias in the treatment of pain, with minority groups receiving less and delayed pain medication compared with their white counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…Patients with self-perceived higher levels of stigma noted increased levels of fatigue, anger, anxiety, and depression. 12 The findings of this study were confirmed with our survey, which showed that some of the barriers to patient care were that patients were in pain, tired, fearful, and angry or frustrated. This is further exacerbated by the well-documented racial and ethnic bias in the treatment of pain, with minority groups receiving less and delayed pain medication compared with their white counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…Depressive symptoms, including feeling hopeless and loss of interest in daily activities, have been positively associated with internalized stigma in people with SCD (Holloway et al, 2016). Additionally, individuals who experience high rates of stigma are more likely to report anxiety, depressive symptomatology, stress, and anger in comparison to those reporting low rates of stigma (M. Ezenwa et al, 2016; Mathur et al, 2016).…”
Section: Domainsmentioning
confidence: 99%
“…Similarly, one study found that patients who report high levels of health-related stigma are more likely to report increased fatigue, anger, anxiety, and depression compared to patients who report lower levels of stigma. However, the patient groups in the study did not differ in terms of pain intensity (Ezenwa et al, 2016).…”
Section: Introductionmentioning
confidence: 84%